Redox homeostasis modulation using theranostic AIE nanoparticles results in positive-feedback drug accumulation and enhanced drug penetration to combat drug-resistant cancer. (December 2022) - Chen, Shaoqing; Wang, Ziyu; Liu, Li; Li, Yuting; Ni, Xinye; Yuan, Hong; Wang, Cheng
Abstract: Drug-resistant cancers usually have multiple barriers to compromise the effect of therapies, of which multidrug-resistance (MDR) phenotype as the intracellular barrier and dense tumor matrix as the extracellular barrier, significantly contribute to the poor anticancer performance of current drug delivery systems (DDS). Here in this study, we fabricated a novel aggregation-induced emission (AIE)-active polymer capable of self-assembling into ultrasmall nanoparticles (∼20 ​nm) with D-alpha Tocopheryl Polyethylene Glycol Succinate (TPGS), for dual-encapsulating of doxorubicin (Dox) and sulforaphane (SFN) (AT/Dox/SFN). It revealed that redox homeostasis modulation of MDR cells (MCF-7/Adr) using AT/Dox/SFN can trigger mitochondria damage and ATP deficiency, which reverse the MDR phenotype of MCF-7/Adr cells to afford enhanced cellular uptake of both drug and DDS in a positive-feedback manner. The enhanced cellular drug accumulation further initiates the "neighboring effect" for improved drug penetration. Using this strategy, the growth of in vivo MCF-7/Adr tumors can be effectively inhibited at a low dosage (1/5) of doxorubicin (Dox) as compared to free Dox. In summary, we offer a new approach to overcome both the intracellular and extracellular barriers of drug-resistant cancers and elucidate the potential action mechanisms, which are beneficial for better cancer management. Graphical abstract: Image 1 Highlights: Redox homeostasis modulation in MDR cancer cell results in positive-feedback drug accumulation and enhanced drug penetration. Mitochondria damage and neighboring effect is responsible for MDR reversal and enhanced drug penetration, respectively. AT/Dox/SFN effectively inhibits ​ in vivo  ​MCF-7/Adr tumors at a low dosage (1/5) of doxorubicin (Dox) as compared to free Dox.